Correction to: AIVariant: a deep learning-based somatic variant detector for highly contaminated tumor samples (Experimental & Molecular Medicine, (2023), 55, 8, (1734-1742), 10.1038/s12276-023-01049-2) - Jeon, Hyeonseong; Ahn, Junhak; Na, Byunggook; Hong, Soona; Sael, Lee; Kim, Sun; Yoon, Sungroh; Baek, Daehyun (Experimental and Molecular Medicine, 2025)
Correction to: Experimental & Molecular Medicine (2023) 55: 1734–1742 https://doi.org/10.1038/s12276-023-01049-2; Article published online 01 August 2023 In this Article, the funding from ‘the Technology development Program, funded by the Ministry of SMEs and Startups, Republic of Korea (RS-2023-00258711)’ was omitted. The correct statement of this Article should have read as below. “We express our gratitude to Sangho Park from Genome4me Inc. for valuable advice and fruitful discussions regarding software development and optimization for AIVariant. This study was supported by the National Research Foundation of Korea (NRF), funded by the Ministry of Science and ICT, Republic of Korea (NRF-2014M3C9A3063541, NRF-2019M3E5D3073104, NRF-2020R1A2C3007032, NRF-2020R1A5A1018081, and NRF-2022M3A9I2082294), by the Korea Health Industry Development Institute (KHIDI), funded by the Ministry of Health and Welfare, Republic of Korea (HI15C3224), by the Technology development Program, funded by the Ministry of SMEs and Startups, Republic of Korea (RS-2023-00258711), and by KREONET (Korea Research Environment Open NETwork), managed and operated by KISTI (Korea Institute of Science and Technology Information).” The original Article has been corrected.